The posthuman condition : consciousness beyond the brain - Pepperell, Robert (Intellect, 2003)
Synthetic creativity, organic computers, genetic modification, intelligent machines & endash; such ideas are deeply challenging to many of our traditional assumptions about human uniqueness and superiority. But, ironically, it is our very capacity for technological invention that has secured us so dominant a position in the world which may lead ultimately to (as some have put it) 'The End of Man'. If we are really capable of creating entities that exceed our own skills and intellect then the consequences for humanity are almost inconceivable. Nevertheless, we must now face up to the possibility.